Perkembangan Kemampuan Bahasa Reseptif Anak Usia 4-5 Tahun Melalui Penerapan Metode Read Aloud - Salsabela, Emsya; Sundari, Nenden; Arzaqi, Roby Naufal (JEA (Jurnal Edukasi AUD), 2024)
Receptive language ability needs to be considered in early childhood, so that listening to understand the language that children hear. This study aims to describe the application of the read-aloud method in TK Islam El-Fash, South Tangerang City, its role in children's receptive language development of children aged 4-5 years. This research uses qualitative, with descriptive research methods, with 5 research participants. The data collection techniques used observation, interviews, and documentation. The result indicates the application of the read-aloud method with the teacher's consideration in choosing picture storybooks based on picture storybooks that are chosen to have fewer words, more pictures, and story content adapted to the conditions and the child's immediate environment, child involvement choosing story ideas. There are supporting factors, training that teachers have received, the availability of library space, and children's reading books. The inhibiting factors are if at the beginning of the school year, conditioning motivation is needed so that children are orderly when the teacher applies the read-aloud method and the need for a quality reading book collection. The impact of applying the read-aloud method can develop children's receptive language skills.